2014
DOI: 10.1093/jjco/hyu156
|View full text |Cite
|
Sign up to set email alerts
|

Brain Metastases in Breast Cancer

Abstract: Brain metastases are less common than bone or visceral metastases in patients with breast cancer. The overall prognosis of breast cancer patients with brain metastases remains poor, and these metastases are less responsive to systemic therapies. Brain metastasis is associated with a reduced quality of life due to progressive neurologic impairments. Recently, a trend of increased incidence of brain metastases in breast cancer has been noted. Reasons for this increased incidence include the more frequent use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 95 publications
0
29
0
Order By: Relevance
“…In most cases, vision preservation was achieved. In comparison, the median survival for BC with brain metastases is 7–10 months . Thus, OM appear to portend a longer survival time than brain metastases.…”
Section: Discussionmentioning
confidence: 94%
“…In most cases, vision preservation was achieved. In comparison, the median survival for BC with brain metastases is 7–10 months . Thus, OM appear to portend a longer survival time than brain metastases.…”
Section: Discussionmentioning
confidence: 94%
“…The incidence of brain metastasis detection in breast cancer is increasing due to advances in imaging technologies and the introduction of novel therapies resulting in longer survival times (9,19). In-depth understanding of the natural history of brain metastases can aid in the optimization of treatment and follow-up strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Brain metastases usually occur late in the disease course of breast cancer, and are uncommon at the time of initial diagnosis of breast cancer (2,3). The risk factors for brain metastases include young age, tumor stage, human epidermal growth factor receptor (HER2)-positivity, triple-negativity, number of metastatic sites (n>2) and large tumor size (49). It has been estimated that 10–15% of patients with breast cancer will develop brain metastases (10), while postmortem studies have detected brain metastases in up to 30% of patients (11).…”
Section: Introductionmentioning
confidence: 99%
“…[81] In patients with breast cancer BM are less common than bone or visceral metastases and frequently represent a late event; nevertheless, up to 16% of metastatic breast cancer patients develop clinically significant BM while autopsy studies showed that up to 30% of patients actually develop brain disease. [3,82] Several risk factors have been associated with the development of BM in patients with metastatic breast cancer, particularly the young age (35 . [83] Patients with HER2-positive metastatic breast tumors are 2-4 times more likely to develop CNS tumors than patients with HER2-negative disease [82] and patients with triple negative breast cancer and basal like breast cancer (BLBC) also appear to be at a high risk for developing BM.…”
Section: Breast Cancermentioning
confidence: 99%
“…[3,82] Several risk factors have been associated with the development of BM in patients with metastatic breast cancer, particularly the young age (35 . [83] Patients with HER2-positive metastatic breast tumors are 2-4 times more likely to develop CNS tumors than patients with HER2-negative disease [82] and patients with triple negative breast cancer and basal like breast cancer (BLBC) also appear to be at a high risk for developing BM. [84] The HER2/neu gene is amplified in 20-25% of primary breast cancer cases; however, gene expression profiles can vary between the primary tumor and metastatic formations and therefore it could not be correct to assume that the HER2 status of the metastatic tumor reflects that of the primary tumor.…”
Section: Breast Cancermentioning
confidence: 99%